PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JURUSAN BAGI MAHASISWA BARU MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCESS (Studi Kasus: STMIK PalComTech Palembang) - Andri Saputra (Teknomatika, 2013)
STMIK PalComTech Palembang, there are two courses namely computer engineering, and information systems, computer engineering courses at the PalComTech more leads to STMIK computer network while more information system study program leading to a programming language, it is so influential once on students will take courses they are interested in, which is often the case they are often confused in taking the courses they wish to attend. There were students and sometimes the wrong chose the course because it is not in accordance with their interests, so that there is a college students not finished half way, or finished College with less satisfying results. A decision support system (CMS) is a system designed to help rather than replace the role of decision maker (the decision makers) in determining a system's decision but rather to provide a decision by increasing its effectiveness in taking a decision in solving a problem. The decision support system of departments is expected to solve the problem where the admission of new students at the beginning of this system will give the decision the Department which is more appropriate for them, the next expected in the process of learning and teaching a College Professor or lecturer is not too difficult in giving science as it has been in accordance with their interests.